Binary collisions between slurry droplets at different ambient temperatures; International Journal of Heat and Mass Transfer; Vol. 259 - Islamova A. G. Anastasiya Gomilievna; Kropotova S. S. Svetlana Sergeevna; Klimenko A. Andrey; Shulyaev S. A. Stanislav Antonovich (2026, 2026)
Title screen